Assessing elements of potential tourism resources in a historic city from host community and tourists’ viewpoints: A perspective from Iran - Dehghan Pour Farashah, Mohammadhossein; Aslani, Ehsan (Turyzm/Tourism, 2021)
After the inscription of the Historic City of Yazd on UNESCO’s World Heritage List in 2017, the number of visiting tourists increased. This area is a set of neighborhoods with unique characteristics. This study is aimed at assessing both the host community’s attitudes towards tourism and the destination image in tourists' perception, as elements of potential tourism resources in the Fahadan neighborhood in Yazd. The present research is descriptive-analytical and a survey was used for data collection with different questionnaires distributed among 170 individuals of the host community and the same number of tourists. For each, three components were considered to assess potential tourism resources. The data extracted from the questionnaires were analyzed using SPSS software. The findings revealed that “impacts of the inscription on the neighborhood” was the most important component for the host community, and “local capacities” for the tourists. In sum, “local capacities” was also ranked higher than the other five components. According to the results, the inefficiency of tourism organizations and authorities in managing and monitoring the processes was responsible for their inability to attract tourists despite the cultural and architectural richness of the studied area and the positive perception of the host community toward tourism.